Valorization of Sal Deoiled Cake as Media for Acidic Amylase and Invertase Co‐Production by Aspergillus niger NJ‐1: Optimization by Response Surface Methodology and Application in Oligosaccharide Synthesis. Issue 6 (14th May 2015) - Singh, Samsher; Gupta, Neetu; Kaur, Jasdeep; Gupta, Anshu
Abstract: Valorization of Sal deoiled cake (DOC) was studied by using it as cheap nutrient source for the co‐production and statistical optimization of two carbohydrases, acidic amylase and invertase, using a newly isolated strain A spergillus niger NJ‐1 and assessment of produced enzymes in oligosaccharides synthesis. Initially, 4% (w/v) of Sal DOC and incubation time of 120 h were found to be the best for optimum enzymes production. Statistical optimization using Plackett–Burman design involved 11 important variables among which five were further optimized by central composite design. Peptone played important role in enzymes co‐production. Both enzymes were stable at acidic pH of 3.0 and 50C temperature. After optimization, amylase and invertase titers increased to ninefold (9.63 IU/mL) and 19‐fold (9.96 IU/mL) compared with unoptimized conditions. Amylase produced maltotrioses and maltopentoses while invertase was able to form kestose during enzymatic hydrolysis. Practical Applications: Acidic amylase and invertase co‐produced may find suitable applications in starch hydrolysis and confectionary industries. Peptone interaction may unlock molecular switch between production levels of two industrially important enzymes. This is the first report on the use of forest by‐product Sal deoiled cake as media for simultaneous production of acidic amylase and invertase.